Identifikasi Senyawa Metabolit Ekstrak Akar Padi dan Potensi Alelopati terhadap Gulma Echinochloa crus-galli dan Monochoria vaginalis - Sujinah, Sujinah; Guntoro, Dwi; Sugiyanta, Sugiyanta (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2021)
Allelopathy plays an important role in weed control because it reduces dependence use on synthetic herbicide and labor. Some rice varieties release chemical compounds that can inhibit weed growth. The objective of this research was to identify compounds and to determine the rice allelopathic potential of rice root extract. The experiment was conducted in Regional Health Laboratorium Jakarta and ICRR’s greenhouse, West Java. Identification of metabolite compounds in 10 rice root extracts used GCMS. The experiment in the greenhouse used a split plot design with four replications. The main plot was weeds (Echinochloa crus-galli and Monochoria vaginalis), while the subplot was the roots of 10 swamp rice varieties and control. The rice roots were extracted by the maceration method using 80% methanol and evaporated by a rotary evaporator. The root extract was diluted distilled water at a 50% concentration (w/v) and applied to weeds. The experimental unit was 3 pots planted with 5 weed seeds. The research identified 88 compounds in rice root extract and the highest peak area was stigmasterol compound. The inhibitory of growth and dry weight of weeds varied, between 27-44%. Inpara-3, Inpara-4, Inpara-7, Inpara-8, and Inpara-10 were able to inhibit weeds greater and belong to one cluster. The five swamp rice can be chosen to be developed in paddy fields that were dominated by Echinochloa crus-galli and Monochoria vaginalis.